The Artistic Expression and Aesthetic Creation in the Arts Learning of The Floating School in the Study of Ki Hadjar Dewantara's Pendidikan Kesenian - Rumi, Jalaluddin; Wadiyo, Wadiyo; Triyanto, Triyanto (Universitas Negeri Semarang, 2019)
The dimension and power of the arts reviewed from an artistic and aesthetic aspect of this article are assessed by its empowerment in the educational process as a teaching and creating medium in The Floating School (TFS) to the discourse toward the arts education problematic holistically. This primary subject constitutes a base of the study to analyze the idea of TFS founders and facilitators to the artistic and aesthetic aspect in its learning object and model, in the study of Ki Hadjar Dewantara’s Pendidikan Kesenian (arts education). The research on this article uses a qualitative-interpretative approach with a study case model to the TFS 2017 program. The viewpoint and understanding of founders and facilitators become a primary data collection through a review of the study document, an applied of a deep interview, and a base of participative observation. The validity of the data collection result is tested by the commensurability test of the data and data resources. By focusing the data on an account and transcript of the interview, data analysis uses an illustrative method through five stages: (1) appreciating the account and transcript of interview; (2) giving a note; (3) formulating a theme; (4) conceptualizing a topic; and (5) adjusting a problem topic, to narrating the result of interpretation with the critical discourse analysis. Thereby, this article shows that the TFS art workshops have a position and role in accompanying and fostering the students to express a story or their understanding of object material and create a message or their processing into the artwork. Those processes and progress finally develop the TFS student’s curiosity and confidence in cultivating their skills and knowledge. This study case is expected to be a power and contribution towards a discipline of arts education.